Organic conjugated fused ring polymer positive electrode material, preparation method thereof and application of organic conjugated fused ring polymer positive electrode material in wide-temperature-range aqueous zinc ion battery

By using organic conjugated condensed ring polymer as the positive electrode material in water-zinc ion batteries, the problem of capacity loss and failure risks of battery in harsh environments is solved, and electrochemical properties with high magnification, high cycling stability and weather resistance are achieved.

CN119552356AInactive Publication Date: 2025-03-04YANGJIANG JIAOTONG ZHUOYUE NEW ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411724124.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing water-zinc ion batteries face huge capacity losses and battery failure risks in harsh environments. Especially under low and high temperature conditions, the ionic conductivity and electron conductivity of the electrode materials are reduced, resulting in slow reaction kinetics and side reactions and structural collapses become problems.

Method used

Using organic conjugated fused ring polymer as the positive electrode material, the triacid anhydride and phenazine of benzene hexacarboxylic acid are reacted under Lewis acid catalysis to prepare a polymer material with a conjugated planar ring structure. The material is prepared by solid phase reaction method and obtained by a multi-step washing and drying process.

Benefits of technology

The organic conjugated condensed ring polymer positive electrode material exhibits high magnification, high cycling stability and excellent weather resistance in a wide temperature domain, significantly improving the comprehensive electrochemical performance of aqueous zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552356A_ABST
    Figure CN119552356A_ABST
Patent Text Reader

Abstract

The invention discloses an organic conjugated fused ring polymer positive electrode material, and relates to the technical field of batteries. The molecular structural formula of the organic conjugated fused ring polymer positive electrode material is # imgabs0 #. The invention also provides a preparation method of the organic conjugated fused ring polymer positive electrode material and application of the organic conjugated fused ring polymer positive electrode material in a wide-temperature-range aqueous zinc ion battery. The raw materials used in the invention are green and environment-friendly, the price is low, the preparation process is simple, and when the positive electrode material is used as an aqueous zinc ion battery positive electrode material, excellent electrochemical properties such as high magnification, high cycle stability and excellent weather resistance can be realized. Therefore, the method is very suitable for large-scale popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to an organic conjugated condensed ring polymer positive electrode material, a preparation method thereof, and an application thereof in a wide temperature range aqueous zinc ion battery. Background Art

[0002] As modern society increasingly relies on renewable energy, it is urgent to develop efficient and safe clean energy storage technology. However, according to the current situation, most clean energy is located in harsh environmental areas, so the supporting energy storage system must meet strict conditions (temperature range: -50℃ to 50℃). Aqueous zinc ion batteries (AZIBs) are rich in resources, environmentally friendly, have good redox potential (-0.76Vvs SHE), 820mAh﹒ g -1 Due to their high theoretical capacity and fast kinetics, they are becoming more and more popular. However, due to the lack of suitable electrode materials, they suffer from huge capacity loss and battery failure risks in harsh environments. It is reported that the reasons for the poor performance of electrode materials at high / low temperatures are as follows:

[0003] 1) At low temperatures, the ionic and electronic conductivity of electrode materials decrease, limiting the charge transfer kinetics, resulting in higher reaction energy barriers and slow reaction kinetics;

[0004] 2) At high temperatures, side reactions, electrode material dissolution, and structural collapse become problems. However, designing electrode materials with high conductivity at low temperatures, high temperature stability, high capacity, and fast reaction kinetics is a practical difficulty.

[0005] Organic electrode materials are composed only of sustainable elements (such as C, H, O, N and S) and can be obtained through artificial synthesis or abundant biomass resources. Compared with inorganic materials, organic materials can be synthesized with high specific capacity through molecular structure design, thus breaking through the energy density limitations of traditional inorganic materials. In addition, the structure of organic materials can also be flexibly designed, which helps to controllably customize their physical properties and electrochemical performance. Moreover, the redox chemistry in ZIBs organic electrode materials is only accompanied by the rearrangement of chemical bonds, rather than the large hydrated Zn 2+ The insertion / extraction of organic materials avoids the large structural changes often found in inorganic compounds. Therefore, organic materials are considered to be promising cathode materials for aqueous ZIBs.

[0006] However, small organic molecules and their intermediate products are easily soluble in the electrolyte during the charge and discharge process, and the conductivity of organic electrode materials is too low, resulting in low cycle stability and poor cycle life of organic electrode materials. In addition, due to the limited ion diffusion kinetics of electrode materials at low temperatures, the electrochemical performance of electrode materials at low temperatures is greatly limited. These factors limit the application of organic electrode materials under various operating conditions.

[0007] Although strategies such as combining organic materials with insoluble matrices can limit the dissolution of electrode materials and improve conductivity, their capacity, rate, cycle performance and weather resistance still cannot meet the requirements. Therefore, obtaining electrode materials with stable structure and fast diffusion kinetics through molecular design is of great significance to enhance the comprehensive electrochemical performance of materials. Summary of the invention

[0008] The invention discloses an organic conjugated condensed ring polymer positive electrode material and a preparation method thereof and application in a wide temperature range aqueous zinc ion battery, which has excellent electrochemical properties such as high rate, high cycle stability and excellent weather resistance.

[0009] The technical solution adopted by the present invention is as follows:

[0010] One of the purposes of the present invention is to provide an organic conjugated fused-ring polymer positive electrode material, the molecular structure of which is:

[0011]

[0012] The second object of the present invention is to provide a method for preparing the above-mentioned organic conjugated fused-ring polymer positive electrode material, comprising the following steps:

[0013] (1) using mellitic acid trianhydride and phenazine as reaction raw materials and Lewis acid as catalyst, the three substances are mixed and ground; the molar ratio of mellitic acid trianhydride, phenazine and Lewis acid is 1:1.5-2:5-10;

[0014] (2) heating the ground mixture under an inert atmosphere to allow mellitic acid trianhydride and phenazine to fully react to obtain a crude product;

[0015] (3) Grinding the crude product, and then washing and drying in sequence to obtain an organic conjugated fused-ring polymer positive electrode material.

[0016] Preferably, the Lewis acid is anhydrous zinc chloride.

[0017] Specifically, the step (2) comprises the following steps:

[0018] (201) adding the mixture into a glass sealed tube, replacing the air in the glass sealed tube with an inert gas, and then sealing the glass sealed tube;

[0019] (202) The sealed glass tube was placed in a muffle furnace, heated to 290-320 °C, and heated to react for 20-24 h. After the reaction was completed, the tube was cooled to room temperature to obtain a crude product.

[0020] Preferably, the inert gas is nitrogen and / or argon.

[0021] Furthermore, in step (3), the washing process is as follows:

[0022] (a) slowly adding 10% to 15% dilute hydrochloric acid to the ground crude product in an ice water bath and stirring until the Lewis acid is removed;

[0023] (b) adding deionized water, the first organic solvent, the second organic solvent and the third organic solvent in sequence, stirring for 6 to 12 hours, and performing suction filtration and washing.

[0024] Preferably, the first organic solvent, the second organic solvent and the third organic solvent are anhydrous ethanol, toluene and DMF respectively.

[0025] Furthermore, in the step (3), the washed product is dried under vacuum conditions at a drying temperature of 70 to 100° C. for a drying time of 12 to 24 hours.

[0026] The third object of the present invention is to provide the application of the above-mentioned organic conjugated fused-ring polymer positive electrode material in a wide temperature range aqueous zinc ion battery.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] (1) The present invention uses mellitic acid trianhydride and phenazine as reaction raw materials to prepare a polymer material with a conjugated planar ring structure, which can enhance the interaction between molecules and show extremely strong structural stability. When this polymer material is used as a positive electrode material, it is not only beneficial to accelerate the transfer of charges, but also can improve the conductivity and ion diffusion dynamics. Experiments have shown that when this polymer material is used as a positive electrode material for aqueous zinc ion batteries (especially wide temperature range aqueous zinc ion batteries), it exhibits a high reversible capacity (at room temperature 25°C: 230mAh﹒g -1 ; High temperature 50℃: 236mAh﹒ g -1 ; Low temperature -50℃: 175mAh﹒ g -1 ), long cycle life (5000 cycles), excellent rate performance and other battery characteristics, make the aqueous zinc ion battery show better comprehensive electrochemical performance (high rate, high cycle stability and excellent weather resistance).

[0029] (2) The organic polymer material prepared by the present invention not only has low raw material cost and is environmentally friendly, but also has a simple preparation process. Therefore, the present invention provides a feasible strategy for realizing the green and low-cost application of organic materials in aqueous zinc ion batteries, and has broad application prospects in the field of aqueous zinc electricity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a schematic diagram of the preparation principle of the polymer material in Example 1 of the present invention.

[0031] Figure 2 This is the SEM image of the polymer material in Example 1 of the present invention.

[0032] Figure 3 The infrared spectrum of the polymer material and the infrared spectrum of the monomer in Example 1 of the present invention.

[0033] Figure 4 The XRD patterns of the polymer material and the monomer in Example 1 of the present invention are shown in FIG.

[0034] Figure 5 This is a constant current charge and discharge curve diagram of an aqueous zinc ion battery using a polymer material as a positive electrode material at different temperatures in Example 4 of the present invention.

[0035] Figure 6 The aqueous zinc ion battery with the polymer material as the positive electrode material in Example 4 of the present invention is at a current density of 0.1A. -1 And the cycle performance diagram at different temperatures.

[0036] Figure 7 This is a rate performance diagram of an aqueous zinc ion battery using a polymer material as a positive electrode material at different current densities in Example 4 of the present invention.

[0037] Figure 8 The aqueous zinc ion battery with the polymer material as the positive electrode material in Example 4 of the present invention is at a current density of 0.1A -1 Long cycle performance diagram at different times and temperatures.

[0038] Fig. 9 This is a comparison chart of the ion diffusion coefficients of an aqueous zinc ion battery using a polymer material as a positive electrode material at room temperature and low temperature in Example 4 of the present invention. DETAILED DESCRIPTION

[0039] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with various embodiments.

[0040] Example 1

[0041] This embodiment provides an organic conjugated fused ring polymer positive electrode material. Based on the Friedel-Crafts reaction mechanism, an organic polymer with a planar cyclic molecular structure is prepared by a solid phase reaction method using mellitic acid trianhydride and phenazine as raw materials and Lewis acid as a catalyst. The molecular structure is as follows:

[0042]

[0043] Figure 1 The preparation principle of the above-mentioned organic conjugated fused ring polymer material is demonstrated. The whole preparation process is as follows:

[0044] First, 1 mmol of mellitic acid trianhydride, 1.5 mmol of phenazine and 5 mmol of anhydrous zinc chloride were weighed and mixed and ground evenly in a glove box.

[0045] Then, the mixture was added to a glass sealed tube, the air in the glass sealed tube was replaced with nitrogen, and the glass sealed tube was sealed at high temperature. Next, the sealed tube was placed in a muffle furnace, heated to 300°C, and heated to react for 24 hours. After the reaction was completed, it was cooled to room temperature to obtain a black crude product.

[0046] Then, the black crude product was ground into powder, 100 ml of dilute hydrochloric acid (concentration of 10%) was slowly added in an ice-water bath, and stirred overnight (12 hours) under heating conditions to remove zinc chloride. Thereafter, water, anhydrous ethanol, toluene, and DMF were used in sequence for heating and stirring for 6 hours, and then filtered and washed.

[0047] Finally, the washed black product is dried at 80° C. for 12 hours under vacuum conditions to obtain an organic conjugated condensed ring polymer material.

[0048] Figure 2 The microscopic condition of the organic conjugated fused ring polymer material is shown, and it can be seen that the organic conjugated fused ring polymer material presents an obvious particle stacking state.

[0049] Figure 3 The Fourier infrared spectrum of the organic conjugated condensed ring polymer material. According to the Fourier infrared spectrum, the -COOH vibration peak of mellitic acid trianhydride is significantly weakened or disappears, indicating that the carboxyl group participates in the Friedel-Crafts reaction and undergoes a cyclization reaction with the aromatic ring to form a new functional group. The C=N and C=O vibration peaks appear in the spectrum of the final product, indicating that the changes in the above peaks indicate that the raw material has been successfully converted into the target product.

[0050] Figure 4 This is the XRD spectrum of the organic conjugated condensed ring polymer material. It can be seen that the polymer shows an obvious peak width at 26°, showing a graphite-like structure, which is formed by the stacking of aromatic rings. At the same time, no obvious monomer signal peak was found in the XRD spectrum of the polymer, which shows that the polymer was successfully prepared.

[0051] Example 2

[0052] The difference from Example 1 is that in this embodiment:

[0053] (1) Weigh 1 mmol of mellitic acid trianhydride, 2 mmol of phenazine, and 7.5 mmol of anhydrous zinc chloride, mix and grind them evenly in a glove box.

[0054] (2) Argon was used as the inert gas, the temperature was raised to 320°C, and the reaction time was 20 h.

[0055] The remaining steps and parameters are the same as those in Example 1.

[0056] The organic conjugated fused-ring polymer material obtained in this example shows substantially the same physicochemical structure and uniform particle characteristics as those of Example 1, and also exhibits substantially equivalent electrochemical properties to those of Example 1.

[0057] Example 3

[0058] The difference from Example 1 is that in this embodiment:

[0059] (1) Weigh 1 mmol of mellitic acid trianhydride, 2 mmol of phenazine and 10 mmol of anhydrous zinc chloride, mix and grind them evenly in a glove box.

[0060] (2) Argon was used as the inert gas, the temperature was raised to 290°C, and the reaction time was 24 h.

[0061] The remaining steps and parameters are the same as those in Example 1.

[0062] The organic conjugated fused-ring polymer material obtained in this example also exhibits substantially the same physicochemical structure and uniform particle characteristics as those in Example 1, and also exhibits substantially equivalent electrochemical properties as those in Example 1.

[0063] Example 4

[0064] This embodiment provides an aqueous zinc ion battery, which uses the organic conjugated condensed ring polymer material in Example 1 as the positive electrode material to prepare a positive electrode sheet, and then uses existing technology to combine a negative electrode, a separator and an electrolyte to prepare an aqueous zinc ion battery.

[0065] Figure 5 The constant current charge and discharge curves of the aqueous zinc ion battery of this embodiment at different temperatures are shown. The results show that the polymer -1 At a current density of 2.54 W, it showed a high specific capacity and average discharge voltage (0.78 V) at different temperatures (50°C, 25°C and -50°C), and there was no obvious polarization phenomenon, indicating that the polymer has excellent weather resistance.

[0066] Figure 6 The aqueous zinc ion battery of this embodiment is shown to have a current density of 0.1A. -1 The results show that the organic conjugated condensed ring polymer material exhibits a higher specific capacity at different temperatures (225 mAh g at room temperature 25 °C). -1 ; High temperature 50℃: 236mAh﹒ g -1 ; Low temperature -50℃: 175mAh﹒ g -1 ), and the capacity retention rate is very stable, proving that the organic conjugated condensed ring polymer material has a high specific capacity and cycle performance

[0067] Figure 7 The rate performance of the aqueous zinc ion battery of this embodiment at different current densities is demonstrated. The results show that the organic conjugated condensed ring polymer material used maintains a good specific capacity at different rates and temperatures, especially at high rates, it can still maintain high electrochemical performance, demonstrating its excellent rate performance and cycle stability.

[0068] Figure 8 The aqueous zinc ion battery of this embodiment is shown to have a current density of 1A. -1 The figure shows that the cycle performance of the organic conjugated condensed ring polymer material at different temperatures reaches 5000 cycles without obvious capacity loss, which fully demonstrates that the organic conjugated condensed ring polymer material has excellent structural stability.

[0069] Fig. 9 The comparison chart of ion diffusion coefficients of the aqueous zinc ion battery of this embodiment at room temperature and low temperature is shown. Generally, the diffusion rate of ions is low under low temperature conditions. However, the organic conjugated condensed ring polymer material used in this embodiment shows similar diffusion rates under room temperature and low temperature conditions, which is because its unique aromatic condensed ring polymer improves the diffusion rate of ions.

[0070] In summary, the present invention designs a polymer material with a conjugated planar ring structure, which can enhance the interaction between molecules and show extremely strong structural stability. The polymer material is used as a positive electrode material for aqueous zinc ion batteries, which can achieve excellent electrochemical properties such as high rate, high cycle stability and excellent weather resistance. Therefore, compared with the prior art, the present invention has obvious technical progress, outstanding substantive characteristics and significant progress.

[0071] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. An organic conjugated fused-ring polymer positive electrode material, characterized in that: The molecular structure of the positive electrode material is:

2. The method for preparing the organic conjugated fused-ring polymer positive electrode material according to claim 1, characterized in that: The following steps are involved: (1) using mellitic acid trianhydride and phenazine as reaction raw materials and Lewis acid as catalyst, the three substances are mixed and ground; the molar ratio of mellitic acid trianhydride, phenazine and Lewis acid is 1:1.5-2:5-10; (2) heating the ground mixture under an inert atmosphere to allow mellitic acid trianhydride and phenazine to fully react to obtain a crude product; (3) Grinding the crude product, and then washing and drying in sequence to obtain an organic conjugated fused-ring polymer positive electrode material.

3. The method for preparing the organic conjugated fused-ring polymer positive electrode material according to claim 2, characterized in that: The Lewis acid is anhydrous zinc chloride.

4. The method for preparing the organic conjugated fused-ring polymer positive electrode material according to claim 2 or 3, characterized in that: The step (2) comprises the following steps: (201) adding the mixture into a glass sealed tube, replacing the air in the glass sealed tube with an inert gas, and then sealing the glass sealed tube; (202) The sealed glass tube was placed in a muffle furnace, heated to 290-320 °C, and heated to react for 20-24 h. After the reaction was completed, the tube was cooled to room temperature to obtain a crude product.

5. The method for preparing the organic conjugated fused-ring polymer positive electrode material according to claim 4, characterized in that: The inert gas is nitrogen and / or argon.

6. The method for preparing the organic conjugated fused-ring polymer positive electrode material according to claim 2, 3 or 5, characterized in that: In the step (3), the washing process is as follows: (a) slowly adding 10% to 15% dilute hydrochloric acid to the ground crude product in an ice water bath and stirring until the Lewis acid is removed; (b) adding deionized water, the first organic solvent, the second organic solvent and the third organic solvent in sequence, stirring for 6 to 12 hours, and performing suction filtration and washing.

7. The method for preparing the organic conjugated fused-ring polymer positive electrode material according to claim 6, characterized in that: The first organic solvent, the second organic solvent and the third organic solvent are anhydrous ethanol, toluene and DMF respectively.

8. The method for preparing the organic conjugated fused-ring polymer positive electrode material according to claim 2, 3, 5 or 7, characterized in that: In the step (3), the washed product is dried under vacuum conditions at a drying temperature of 70 to 100° C. for a drying time of 12 to 24 hours.

9. Use of the organic conjugated fused-ring polymer positive electrode material according to claim 1 in a wide temperature range aqueous zinc ion battery.

Citation Information

Patent Citations

  • Preparation method of organic microporous polymer electrode material

    CN107317032A

Cited By

  • Aza-aromatic fused ring polymer, preparation method and application of aza-aromatic fused ring polymer in preparation of aqueous zinc ion battery

    CN120923779A